THE BLACK ANGEL OF HISTORY: afrofuturism's cosmic techniques. Issue 4 (3rd July 2020) - Neyrat, Frédéric; Ross, Daniel
Abstract: Against the usual interpretation, which states that Afrofuturism is unreservedly technophilic, I argue that Afrofuturism is a radical critique of white technology. White technology (be it imperial, colonial or capitalist) is an acosmic technology that rejects its belonging to the cosmos. The Space Age and what is now called New Space (both of which have neo-colonial aims) are perfect illustrations of white technology and its anthropocentric enthusiasm. Rejecting this colonial and exploitative technology, Afrofuturism – from the music and poems of Sun Ra to the paintings of Wangechi Mutu to the poems and activism of Alexis Pauline Gumbs – is first and foremost an attempt to use outer space not as a space open to conquest, but as a mediation, a stellar detour thanks to which our terrestrial condition could be politically and anthropologically rethought. At odds with any geoengineering project, Afrofuturism conjures up an "epoch of being" (Heidegger) in which technology would be constantly inhabited by a form of uncanny that would definitively prevent human beings from considering technology as a way of mastering the Earth.